THE ROLE OF VILLAGE OFFICIALS IN UPDATING THE DATA ON BENEFICIARIES IN LEMBAH HIJAU VILLAGE, BONEPANTAI DISTRICT, BONE BOLANGO - Feldi Lasimpala; wilyam Mooduto; Ikbal Kadir (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This final report aims to find out the truth of the data on beneficiaries in Lembah Hijau Village so that there is no more partial or double distribution. The method in this final report uses triangulation data collection techniques consisting of observations, interviews, and documentation. The results showed that the data in Lembah Hijau Village can be said to be good from previous years because according to the report, there are only a few people who have received double assistance. This is due to the lack of communication between the village government and the existing aid assistants.